IMPLEMENTASI PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA HONORER DI PEMERINTAHAN KABUPATEN MAYBRAT - Murary, Weron; Hendri Siahaya, Vector (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Protection of honorary workers is very important, and to continue to ensure the quality of human resources of government officials, the appointment of honorary workers to become candidates for Civil Servants will be carried out through administrative completeness checks after verification and validation for honorary workers whose income is financed from the Regional Revenue and Expenditure Budget. (APBD), a research was conducted on the form of legal protection for honorary workers in the Maybrat district government after the enactment of Government Regulation No. 56 of 2012 concerning the appointment of honorary workers as candidates for civil servants and the mechanism for the appointment of honorary staff to become State Civil Apparatus in Maybrat Regency. The type of research used in this research is normative empirical, the research will be conducted in Maybrat Regency. In conducting the research, the data sources are taken from secondary data and primary data. Secondary data obtained from official documents, books related to the object of research, while primary data obtained directly from the source, either through interviews, observations and reports in the form of unofficial documents which were then processed by researchers. Collecting data through literature study and interviews, then qualitative data analysis by assessing the data that has been obtained in the field to be connected with secondary data and primary data and then a conclusion is drawn. From the results of the study, the authors found that related to protection as Non-PNS or non-PPPK employees, while still serving in government agencies, Honorary Workers were given protection in the form of certainty of the employment status of Honorary Workers, social protection for Honorary Workers, technical protection for honorary workers, then based on Government Regulation Number 56 of 2012 concerning the Appointment of Honorary Personnel to Candidates for Civil Servants (PNS), fulfilling the criteria and requirements; (1) honorary workers who are a maximum of 46 years old and have a continuous working period of 20 years or more, (2) honorary workers who are a maximum of 46 years old and have 10-20 continuous years of service, (3) honorary workers who is a maximum of 40 years old and has a continuous service period of 5-10 years, (4) temporary workers who are a maximum of 35 years old and have a continuous working period of 1-5 years. The appointment of honorary staff to become Civil Servant Candidates is carried out objectively, meaning that this appointment is carried out correctly without being influenced by personal opinions or views or by others, must be carried out based on predetermined conditions, and does not differentiate gender, ethnicity, religion. , race, class or region so that prospective Civil Servants will be obtained who are professional, honest, responsible, neutral, and have competence in accordance with their duties or positions.Keywords: Protection, Honor, Maybrat Kabupaten County.